2016
DOI: 10.1126/scisignal.aad8953
|View full text |Cite
|
Sign up to set email alerts
|

ROCK2 signaling is required to induce a subset of T follicular helper cells through opposing effects on STATs in autoimmune settings

Abstract: Rho-associated kinase 2 (ROCK2) determines the balance between human T helper 17 (TH17) cells and regulatory T (Treg) cells. We investigated its role in the generation of T follicular helper (TFH) cellswhich provide help necessary to generate antibody-producing B cells in normal and autoimmune conditionsWe found that targeting ROCK2 in normal human T cells or peripheral blood mononuclear cells (PBMCs) from patients with active systemic lupus erythematosus (SLE) decreased the number and function of Tfh cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 45 publications
4
39
0
Order By: Relevance
“…In agreement with previous findings in animal models and Th17-skewing in vitro culture of human T cells (15)(16)(17), this study further confirmed the potential of selective ROCK2 inhibition to downregulate autoimmune-driven pathology via shifting the balance between proinflammatory and anti-inflammatory immune cell responses. Although the clinical improvement achieved in the same time span by treatment with KD025 was not as robust as the response seen with other oral treatments, such as methotrexate, JAK inhibitors, and apremilast, or newer biologics neutralizing cytokines in the Th17 pathway, future randomized trials of KD025 carried out for a longer time period (to account for a different molecular mechanism of action) in a larger population of psoriatic patients are required to further validate the therapeutic potential and risk-benefit profile of targeted ROCK2 inhibition in psoriasis.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In agreement with previous findings in animal models and Th17-skewing in vitro culture of human T cells (15)(16)(17), this study further confirmed the potential of selective ROCK2 inhibition to downregulate autoimmune-driven pathology via shifting the balance between proinflammatory and anti-inflammatory immune cell responses. Although the clinical improvement achieved in the same time span by treatment with KD025 was not as robust as the response seen with other oral treatments, such as methotrexate, JAK inhibitors, and apremilast, or newer biologics neutralizing cytokines in the Th17 pathway, future randomized trials of KD025 carried out for a longer time period (to account for a different molecular mechanism of action) in a larger population of psoriatic patients are required to further validate the therapeutic potential and risk-benefit profile of targeted ROCK2 inhibition in psoriasis.…”
Section: Resultssupporting
confidence: 79%
“…ROCK2 is induced during Th17-skewing conditions and regulates IL-17 secretion via a STAT3/IRF4/RORgtdependent mechanism in mice and humans (13,(15)(16)(17). Histological assessment revealed that baseline pSTAT3, IRF4, RORgt, and ROCK2 staining were greater, whereas ROCK1 expression was diminished in lesional skin in comparison with nonlesional skin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with prior observations demonstrating that the selective ROCK2 inhibitor, KD025, can downregulate the production of IL-17 and IL-21 by RA T cells, KD025 decreased the production of these cytokines by SLE T cells, although the production of IFNγ appears to be ROCK2 dependent in RA but not in SLE T cells 18. The ability of KD025 to target IL-17A and IL-21 production in our study was, however, not accompanied by decreases in Stat3 phosphorylation or IRF4 expression,18 36 possibly due to the later timing of addition of the ROCK2 inhibitor to the cultures, which may have enabled the initial wave of signalling events to be protected from the inhibitory effects of KD025.…”
Section: Discussionmentioning
confidence: 46%
“…Dual RORγt or STAT3 pathway inhibitors have been developed, such as the small GTPase, ρ-associated coiled-coil containing protein kinase 2 (Rock2) inhibitor, KD025. We recently showed that KD025 was efficient in suppressing murine and human cGvHD through inhibition of RORγt and STAT3, leading to reduced IL-17 and IL-21 cytokine production and T follicular helper (TFH) cells that can support pathogenic antibody production during cGvHD (31,37). Via its effects on STAT5, Treg production also is facilitated (31,38).…”
Section: Introductionmentioning
confidence: 99%